A systematic review of the literature on telepsychiatry for bipolar disorder. Issue 10 (14th September 2022) - Farrell, Abigail; George, Nevita; Amado, Selen; Wozniak, Janet
Abstract: Objective: Bipolar (BP) disorder is a highly morbid disorder that is often misdiagnosed or undiagnosed and affects a large number of adults and children. Due to the coronavirus disease 2019 public health emergency stay at home orders, most outpatient mental health care was provided via telepsychiatry, and the many benefits of virtual care ensure that this will continue as an ongoing practice. The main aim of this review was to investigate what is currently known about the use of telepsychiatry services in the diagnosis and treatment of BP disorder across the lifespan. Method: A systematic literature review assessing the use of telepsychiatry in BP disorder was conducted in PubMed, PsychINFO, and Medline. Results: Six articles were included in the final review. All included articles assessed populations aged 17 years or older. The literature indicates that BP disorder was addressed in telepsychiatry services at a similar rate as in‐person services, reliable diagnoses can be made using remote interviews, satisfaction rates are comparable to in‐person services, telepsychiatry services are able to reach and impact patients with BP disorder, are sustainable, and patient outcomes can improve using a telepsychiatry intervention. Conclusions: Given the morbidity of BP disorder, the research addressing the telepsychiatry diagnosis and treatment of BP disorder is sparse, with only emerging evidence of its reliability, effectiveness, and acceptance. There is no research assessing the safety and efficacy of telepsychiatry in pediatric populations with BP disorder. Given the morbidity associated with BP disorder at any age, further research is needed to determine how to safely and effectively incorporate telepsychiatry into clinical care for BP adult and pediatric patients. Graphical Abstract: A photo has been provided for the graphical understanding. It is the author's understanding that a short summary of the main findings is to accompany this for the table of contents. Here is a brief summary to be added with the graphical abstract: Given the morbidity of BP disorder, the research addressing the telepsychiatry diagnosis and treatment of BP disorder is sparse, with only emerging evidence of its reliability, effectiveness, and acceptance. There is no research assessing the safety and efficacy of telepsychiatry in pediatric populations with BP disorder. Giver the morbidity associated with BP disorder at any age, further research is needed to determine how to safely and effectively incorporate telepsychiatry into clinical care for BP adult and pediatric patients.